Global burden, point sources, and outbreak management of healthcare-associated Burkholderia cepacia infections: An integrative review. (July 2020) - Shaban, Ramon Z.; Sotomayor-Castillo, Cristina; Nahidi, Shizar; Li, Cecilia; Macbeth, Deborough; Mitchell, Brett G.; Russo, Philip L.
Abstract: Objective: To examine the global burden, associated point sources, and successful prevention and control measures for documented outbreaks of Burkholderia cepacia healthcare-associated infections (HAIs). Design: Integrative review. Methods: A review of all outbreaks of Burkholderia cepacia HAIs published in the peer-reviewed literature between January 1970 and October 2019 was conducted to identify the global burden, associated point sources, and successful prevention and control measures using the Guidelines for Outbreak Reports and Intervention Studies of Nosocomial Infections (ORION). Results: In total, we reviewed 125 documented outbreaks of Burkholderia cepacia –related HAIs worldwide. The reported B. cepacia HAIs for this period involved 3, 287 patients. The point sources were identified in most outbreaks of B. cepacia HAIs (n = 93; 74.4%); they included medication vials, disinfectants, and antiseptics. Moreover, 95 of the outbreak reports (76%) described effective prevention and control measures, but only 33 reports indicated the use of a combination of environment-, patient- and staff-related measures. None of the outbreak reports used the ORION guidelines. Conclusions: Outbreaks of Burkholderia cepacia HAIs are an ongoing challenge. They are often associated with immunocompromised patients who acquire the infection from exposure to contaminated medications, products, and equipment. These outbreaks are not infrequent, and a range of infection prevention and control measures have been effective in arresting spread. The use of ORION guidelines for outbreak reporting would improve the quality of information and data to generate evidence for translation into practice.